A one-year proprioceptive exercise programme reduces the incidence of falls in community-dwelling elderly people: A before–after non-randomised intervention study. (December 2016) - Pérez-Ros, Pilar; Martinez-Arnau, Francisco M.; Malafarina, Vincenzo; Tarazona-Santabalbina, Francisco J.
Highlights: Polypharmacy is an independent risk factor for falls in the elderly. Use of beta-blockers was seen to be related to an increase in falls. In this observational study, proprioception exercises reduced the incidence of falls. Abstract: Background: The risk of falls increases with age. Balance alteration and polypharmacy are independent contributors to an increased risk of falls. Objective: The primary aim was to assess whether a proprioceptive exercise programme reduces the incidence of falls. A secondary aim was to assess the association between drugs and falls. Design: This was a before–after non-randomised intervention study. Participants: The study recruited independent and cognitively intact community-dwelling people aged over 69 years, from December 2012 to May 2014. Methods: The intervention was done by a nurse and consisted of a monthly supervised group session of proprioceptive training for 1 year, supplemented by a home diary exercise. Daily medication was reviewed. Results: We included 572 subjects (63.3% women), mean age 76.1 ± 3.9 years. The mean number of drugs prescribed at the start of the study was 4.7 ± 3.0and 353 of the participants (61.7%) were taking four or more drugs a day. The elderly who fell were more dependent in their activities of daily living (Barthel index), and their balance was worse (determined using the Tinetti scale), as were their results on a cognitive scale (the MEC). After the intervention, an increase in self-perceived quality of life (EQ5D) was reported. The incidence of falls was reduced from 37.5% in the 12 months prior to the intervention to 25.7% in the 12 months after the intervention. During the follow-up, beta-blocker use was associated with an increased incidence of falls (OR = 2.05; 95%IC: 1.24–3.39; p = 0.005). In contrast, antiplatelet/anticoagulation drugs were associated with a lower risk of falls (OR = 0.7; 95%IC: 0.55–0.88; p = 0.003). Conclusions: The proprioceptive exercise programme reduced the incidence of falls in community-dwelling older people. Multiple drug use was an independent predictor of an increased risk of falls, and specific drug groups were associated with falls.